CBMT-23. NON-CANONICAL FUNCTIONS OF TERT IN GLIOBLASTOMA. (11th November 2019) - Ferdosi, Shayesteh; Taylor, Brett; Bollam, Saumya; Gokhale, Vijay; Hurley, Laurence; Dhruv, Harshil; Berens, Michael
Abstract: Telomerase is an enzyme with a catalytic subunit, telomerase reverse transcriptase (TERT), that is in charge of telomere elongation in the nucleus. Promotor region of TERT is commonly mutated across cancers, especially in glioblastoma (GBM) with over 80% frequency. In the absence of any effective molecular targeting therapy for GBM, elucidating oncogenic signaling of TERT could open new avenues in GBM treatment. Canonically, mutations of TERT, which result in TERT upregulation, maintain telomere length in the nucleus and promote indefinite proliferation of cancer cells. However, a non-canonical function of TERT in the mitochondria has recently been suggested. We screened GBM cell models against a novel small molecule inhibitor (RG1534, Reglagene Inc.) that interferes with the functionality of a mutated hTERT promoter. RG1534 selectively suppresses glioma cell viability without affecting non-transformed normal human astrocytes. More interestingly, RG1534 treatment leads to rapid apoptosis induction in glioma cell lines that does not correlate with the time course of the telomere shortening effect. We further validated this rapid apoptosis behavior in glioma cell lines using siRNA and CRISPR/Cas-9 mediated hTERT knockdown. We also measured the protein expression of TERT in subcellular fractions of glioma cell lines and demonstrated the presence of higher TERT expression in mitochondrial extract compared to the nucleus. Finally, using MitoSOX dye we assessed ROS generation in glioma cells in response to an oxidant with or without TERT expresssion. In summary, our results demonstrate that non-canonical functions of TERT may play critical role in glioma pathobiology and require more detail investigation.